The Effect Of Sinking Parameters To Optimize Response At Edm Of Aisi H13 Using Taguchi – Fuzzy Method - Diah Kusuma Pratiwi (Journal of Mechanical Science and Engineering, 2017)
The development technology in today's manufacturing is very fast, the desire of the market will need products and components with complex shapes and a high level of accuracy as well as hardness material which has high strength. High degree of hardness and precision widely used non-conventional sinking of EDM. End cutting depth (CDE), the maximum rate of erosion material(REM) and rate of electrode wear (RWE) as well as minimal surface roughness (SR) is the performance of the process of machine sinking EDM to be achieved. Aims of a study conducted to determine the contribution of the process parameters in order to reduce the variation of response parameters simultaneously and determine the value of setting the appropriate parameter process. The parameters were varied current, on time, off time and machining voltage. This research used experimental design of Taguchi method with orthogonal matrix L16 44. Combination of Taguchi-Fuzzy is used as a method of optimization by experimenting as much as two times. Optimization results show the contribution of each parameter on all responses simultaneously is current at 41.35%, energy on time amounted to 37.90%, off time amounting to 10,11%and machining voltage by 5%. End cutting depth (CDE) with a specific target, the maximum rate of erosion material (REM), ), the rate of wear of the electrode (RWE) and the surface roughness (SR) are both derived parameter value of at least current, 15A the energy on time 300ìs, off time 5ìs and machining voltage of 12V.